Sources, levels and methods of potassium application in soil - Sanzonowicz, Cláudio; Mielniczuk, João (Pesquisa Agropecuaria Brasileira, 2014)
A field experiment was carried out on a Red-Yellow Podzolic (Palendult) soil from the Itapoã soil mapping unit at Viamão, RS, Brazil, in 1981/82. to determine the efficiency of K sources (KCl, K2SO4 and KAISiO4 (kalsilite), the methods of application (broadcast with incorporation, in rows, and broadcast on the soil surface) and doses of zero, 150 and 300 kg/ha of K, on dry matter production and K uptake by millet (Pennisetum americanum (L.) Leeke) plants. There was neither effect of sources nor off methods of K application on dry matter production. The effect of K was significant up to the rate of 150kg/ha and 300kg/ha of K, respectively, on dry matter production and K uptake. Methods of application did not show any effect on the K absorption by millet. K absorption was higher when KCl was applied, in comparison with kalsilite application, while K2SO4 showed intermediate and nonsignificant values between these two sources.